Avidity of anti-neurocytoskeletal antibodies in cerebrospinal fluid and serum - Fialová, L; Švarcová, J; Bartos, A; Malbohan, I (Folia microbiologica, 2012)
Antibodies have different avidities that can be evaluated using modified enzyme-linked immunosorbent assay (ELISA) techniques. We determined levels and avidities of antibodies to light (NFL) and medium (NFM) subunits of neurofilaments and tau protein in serum and cerebrospinal fluid (CSF) from 26 patients and anti-tau antibody levels and their avidities in 20 multiple sclerosis (MS) patients and 20 age- and sex-matched controls. Each sample was analyzed using both standard ELISA and also using a similar ELISA protocol with the addition of urea. The avidities of anti-neurocytoskeletal antibodies were higher in the CSF than those in serum (anti-NFL, p < 0.0001; anti-tau, p < 0.01; anti-NFM, n.s.). There was no relationship between avidities in serum and CSF for individual anti-neurocytoskeletal antibodies. We did not observe the relationship among the avidities of various anti-neurocytoskeletal antibodies. The avidities of anti-tau antibodies in the CSF were significantly higher in the MS patients than those in the controls (p < 0.0001). The study demonstrates the differences in avidities of CSF or serum neurocytoskeletal antibodies measured as the urea resistance by ELISA method. Avidity determination of anti-neurocytoskeletal antibodies could contribute to the evaluation of the immunological status of patients.
Keywords: dospělí; afinita protilátek; Female; tau Proteins; imunoglobulin G; Adult; ženské pohlaví; lidé; Multiple Sclerosis; Neurofilament Proteins; roztroušená skleróza; protilátky anti-idiotypické; neurofilamentové proteiny; Immunoglobulin G; Male; Aged; lidé středního věku; proteiny tau; senioři; mužské pohlaví; Antibodies, Anti-Idiotypic; Middle Aged; Antibody Affinity; Humans